Differential expression of drug resistance genes in CD146 positive dental pulp derived stem cells and CD146 negative fibroblasts - Maryam S. Tavangar; Armin Attar; Mahboobeh Razmkhah; Seyed‐Mojtaba Hosseini; Ahmad Hosseini; Ahmad Monabati; Fereshteh Shafiei (Wiley, 2020)
Abstract Introduction The stem cell portion of the dental pulp derived cultures (DPSCs) showed a higher resistance to cytotoxic effect of restorative dental materials compared to pulpal fibroblasts (DPFs). Here, we aimed to compare the expression of some drug resistant genes between these cells. Methods and materials To separate DPSCs from DPFs, we used magnetic cell sorting technique based on CD146 expression. To assess the stem cell properties, the positive and negative portions underwent colony forming assays and were induced to be differentiated into the adipocytes, osteoblasts, hepatocytes, and neural cells. Cell surface antigen panels were checked using immune fluorescence and flow‐cytometry techniques. The mRNA expression of 14 ABC transporters including ABCA2, ABCB1, ABCB11, ABCC1, ABCC2, ABCC3, ABCC4, ABCC5‐2, ABCC5‐4,ABCC5‐13, ABCC6, ABCC10, ABCC11, and ABCG2 genes was assessed, using quantitative RT‐PCR technique. Results Only the CD146 positive portion could be differentiated into the desired fates, and they formed higher colonies (16.7 ± 3.32 vs. 1.7 ± 1.67, p < .001). The cell surface antigen panels were the same, except for CD146 and STRO‐1 markers which were expressed only in the positive portion. Among the ABC transporter genes studied, the positive portion showed a higher expression (approximately two‐fold) of ABCA2, ABCC5‐13, and ABCC5‐2 genes. Conclusion Dental pulp stem cells which can be separated from dental pulp fibroblasts based on CD146 expression, express higher levels of some drug resistance genes which probably accounts for their features of more resistance to cytotoxic effects of some dental materials. This needs to be more validated in future.